2012
DOI: 10.1002/elsc.201100159
|View full text |Cite
|
Sign up to set email alerts
|

Mineral substances and macronutrients in the anaerobic conversion of biomass: An impact evaluation

Abstract: Optimal nutrient supply in the digester is essential for efficient biogas production. The aim of this study was to analyze the effects of various micro‐ and macronutrients on the process stability by a field test. The digestates of 25 biogas plants across the federal state of Baden‐Württemberg, Germany, were investigated. Collected data including trace elements, macronutrients, and volatile fatty acids (VFA) concentrations, as well as the organic loading rate and hydraulic retention time were subjected to stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 29 publications
0
26
0
Order By: Relevance
“…Lack of certain nutrients deteriorates the performance of AD and may change the degradation pathways leading to a build up of intermediary products such as propionate. Results by Vintiloiu et al (2012) showed strong statistically signicant eects of macro-and micro-nutrients on the stability of the anaerobic process of agricultural biogas plants in Germany. Nickel, molybdenum, and sulfur showed the strongest eects, followed by selenium, whereas iron, cobalt and sodium only showed effects in combination with other elements.…”
Section: Methane Production Kineticsmentioning
confidence: 96%
“…Lack of certain nutrients deteriorates the performance of AD and may change the degradation pathways leading to a build up of intermediary products such as propionate. Results by Vintiloiu et al (2012) showed strong statistically signicant eects of macro-and micro-nutrients on the stability of the anaerobic process of agricultural biogas plants in Germany. Nickel, molybdenum, and sulfur showed the strongest eects, followed by selenium, whereas iron, cobalt and sodium only showed effects in combination with other elements.…”
Section: Methane Production Kineticsmentioning
confidence: 96%
“…Together with the fresh maize silage, a certain amount of micronutrients were also added to the reactors, providing necessary nutrients for microbial growth and avoiding biological process disturbances. The dosage and the composition of the micronutrients was based on Vintiloiu et al's [11] recommendation. The maize silage in the leach-bed reactors was slowly decomposed and turned into a leachate rich in organic acids and alcohols.…”
Section: Reactors and Substratementioning
confidence: 99%
“…Adding trace elements to the biogas process has been shown to increase the methane production of the process , Vintiloiu et al 2012. The requirements for a better nutrient balance can be achieved by the co-digestion of energy crops with manure, which contains more trace elements (Cavinato et al 2010), and with a large variation of feedstock, including different variations of organic wastes, which seems to improve the abundance of trace elements (Schattauer et al 2011).…”
Section: Anaerobic Co-digestion Of Energy Cropsmentioning
confidence: 99%